2005
DOI: 10.1038/sj.bjc.6602625
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse EGFR staining is associated with reduced overall survival in locally advanced oesophageal squamous cell cancer

Abstract: Squamous cell carcinoma of the oesophagus (SCCO) is still a pathology of bad prognosis. Specific therapies are now developed against epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2, c-kit receptor (CD117), vascular endothelial growth factor (VEGF) and p53 protein. This study was aimed at assessing their expression in a large series of SCCO, as well as their potential therapeutic interest in this pathology. Immunohistochemical expression of these factors was assessed retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 40 publications
6
85
1
2
Order By: Relevance
“…In patients with head and neck, ovarian, cervical, bladder, and esophageal squamous cell carcinomas, EGFR expression is a strong prognostic indicator that correlates with both higher recurrence rates and shorter survival. [11][12][13]17,21,22,[25][26][27][35][36][37][38] In the current study, we demonstrated that EGFR expression in esophageal adenocarcinoma correlates with outcome in patients who are treated with esophagectomy alone. Our data showed that EGFR expression is correlated strongly with poor overall and disease-free survival in univariate analyses with a trend toward correlation in multivariate analyses.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In patients with head and neck, ovarian, cervical, bladder, and esophageal squamous cell carcinomas, EGFR expression is a strong prognostic indicator that correlates with both higher recurrence rates and shorter survival. [11][12][13]17,21,22,[25][26][27][35][36][37][38] In the current study, we demonstrated that EGFR expression in esophageal adenocarcinoma correlates with outcome in patients who are treated with esophagectomy alone. Our data showed that EGFR expression is correlated strongly with poor overall and disease-free survival in univariate analyses with a trend toward correlation in multivariate analyses.…”
Section: Discussionmentioning
confidence: 92%
“…Patients who had tumors that expressed EGFR had shorter disease-free and overall survival compared with patients who had EGFR-negative tumors, but EGFR expression was not an independent prognostic indicator for either parameter in multivariate analysis. Although there have been several studies of EGFR expression in esophageal squamous cell carcinomas, 21,[25][26][27][35][36][37][38] studies of the role of EGFR in esophageal adenocarcinomas have been limited. 28,29,39 Similar to our studies, the majority of the esophageal adenocarcinomas in previous studies were from the lower one-third of the esophagus or from the GEJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal activation of EGFR promotes tumorigenesis and proliferation through regulating cell signaling transduction, cell proliferation, apoptosis and angiogenesis. Gibault et al (15) demonstrated that EGFR overexpression was significantly correlated with vascular invasion (P=0.023), local recurrence (P=0.006) and a lower survival rate (P=0.003). In addition, a further study found that EGFR inhibitors were able to inhibit the overexpression of EGFR and human epidermal growth factor receptor-2, thereby inhibiting the proliferation of esophageal cancer cell lines (16).…”
Section: Discussionmentioning
confidence: 99%
“…Increased EGFR expression may influence multiple aspects of tumor biology, including survival, proliferation of cells, motility, invasiveness and resistance to treatment (8)(9)(10). The success of active small molecule tyrosine kinase inhibitors (TKIs) targeted against EGFR in treating non-small cell lung cancer (NSCLC) has prompted research into their clinical benefits in numerous other solid tumors.…”
Section: Introductionmentioning
confidence: 99%